St. Kitts and Nevis : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
St. Kitts and Nevis is a small, open economy in the Eastern Caribbean. Hurricane damage and its effects on tourism, sugar industry, construction, and mining and quarrying industry are discussed. Stability in the financial system has supported economic activity in recent years. Overall, capital inflows have covered large current account deficits, allowing for a buildup in imputed international reserves. The rapid growth of offshore financial services has been a major factor behind the diversification of the economic base into services and service-related activities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet